Gut Microbiota and Fecal Levels of Short-Chain Fatty Acids Differ Upon 24-Hour Blood Pressure Levels in Men. Issue 4 (October 2019) - Huart, Justine; Leenders, Justine; Taminiau, Bernard; Descy, Julie; Saint-Remy, Annie; Daube, Georges; Krzesinski, Jean-Marie; Melin, Pierrette; de Tullio, Pascal; Jouret, François
Abstract : Gut microbiota may influence blood pressure (BP), namely via end products of carbohydrate fermentation. After informed consent, male volunteers were prospectively categorized into 3 groups upon European Society of Hypertension criteria based on 24-hour ambulatory BP measurements: (1) hypertension, (2) borderline hypertension, and (3) normotension. Stool, urine and serum samples were collected in fasting conditions. Gut microbiota was characterized by 16S amplicon sequencing. Metabolomics, including quantification of short-chain fatty acids, was conducted using nuclear magnetic resonance. Two-way ANOVA combined with Tukey post hoc test, as well as multiple permutation test and Benjamini-Hochberg-Yekutieli false discovery rate procedure, was used. The cohort included 54 males: 38 hypertensive (including 21 under treatment), 7 borderline, and 9 normotensive. No significant difference was observed between groups concerning age, body mass index, smoking habits, and weekly alcohol consumption. The genus Clostridium sensu stricto 1 positively correlated with BP levels in nontreated patients (n=33). This correlation was significant after multiple permutation tests but was not substantiated following false discovery rate adjustment. Short-chain fatty acid levels were significantly different among groups, with higher stool levels of acetate, butyrate, and propionate in hypertensive versus normotensive individuals. No difference was observed in serum and urine metabolomes. Correlation between stool metabolome and 24-hour BP levels was evidenced, with R 2 reaching 0.9. Our pilot study based on 24-hour ambulatory BP measurements, 16S amplicon sequencing, and metabolomics supports an association between gut microbiota and BP homeostasis, with changes in stool abundance of short-chain fatty acids. Abstract : Supplemental Digital Content is available in the text.